Risk Identification And Assessement In Construction Projects, In Iran - Nasr, Mohammad Tehrani (2010)
The focus of this research study is on exploration and description of identified and prioritized potential risk factors in building construction project in Iran. In addition, this investigation attempts to discover challenges and problems for Risk Identification Process in Iran.